Current state of corporate social responsibility among industrial companies in Malaysia / Tamoi Janggu, Corina Joseph and Nero Madi - Janggu, Tamoi; Joseph, Corina; Madi, Nero (2006)
The main aim ofthis study is to find out the level ofthe current state and trend of CSR of industrial companies in Malaysia. Content analysis method is used to analyse the data from the corporate annual reports of the companies from 1998 to 2003. Spearman rank coefficient is applied to investigate whether or not there is relationship between CSR and companies’ characteristics. It can be concluded that the CSR level of industrial companies in Malaysia is increasing both in terms of amount of the disclosure and the number of participating companies. The most popular theme of disclosure is human resource then followed by environmental information and disclosure on product. An involvement with community ranked last. This implies that companies do appreciate their employees and concern about environmental issues. The statistical analysis, among others, indicates there is positive relationship between CSR and companies’ size (as measured by turnover) but no apparent relationship is noticed with companies’ capital.